Network Design and Optimization in Agri-Food Supply Chain: Application to A Juice Businesss - Belkız Torğul; Enes Demiralay; Turan Paksoy (Journal of Transportation and Logistics)
Lack of access to agriculture-based food has become a major problem that is becoming increasingly widespread. Agri-food supply chains have attracted growing attention from consumers, companies, government agencies, and researchers in recent years due to problems with food safety and related public health issues. Sustainability, which has attracted global attention in recent years, should also be included within the optimal framework of the process of supplying agricultural food, which is among the most important needs people face in order to live healthy lives. One of the most critical factors affecting the agri-food supply chain’s sustainability is network design. Therefore, the design and operation of agri-food supply chains should be subject to stricter regulations. In this study, we conduct a literature review of operational research methods used in the design of agricultural food supply chains, and present a new, closed-loop network design application for supply chain sustainability of peach juice products. The peach juice supply chain network design model was formulated using linear programming to maximize profit and was verified using the GAMS program with the help of a numerical example. The proposed model framework highlights cost reduction activities within the recycling process, protecting the environment, and recovery the waste to the economy while addressing farmer‒supplier selection, transportation, and distribution problems.